2017
DOI: 10.1111/jmg.12287
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic record of collision and collapse in the Ediacaran‐Cambrian Araçuaí orogen, SE‐Brazil: Insights from P–T pseudosections and monazite dating

Abstract: The Araçuaí orogen is the Brazilian counterpart of the Araçuaí‐West Congo orogenic system (AWCO), a component of the Ediacaran‐Cambrian orogenic network formed during the amalgamation of West Gondwana. The northwestern portion of the Araçuaí orogen is dominated by a succession of metasedimentary rocks made up of Meso‐ to Neoproterozoic rift, passive margin and syn‐orogenic sequences, locally intruded by post‐collisional granites. These sequences are involved in three distinct tectonic units, which from west to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 75 publications
(198 reference statements)
0
26
0
1
Order By: Relevance
“…The metasedimentary rocks involved in the western limb record two metamorphic events. A Barrovian metamorphism assisted the D 1 deformation phase with P-T conditions increasing eastwards along the SER-thrust system, and reaching ~8.5 kbar at ~650ºC (Peixoto et al 2018). Age determinations on the monazite indicated that this event took place between 575 and 565 Ma.…”
Section: The Western Limbmentioning
confidence: 94%
See 4 more Smart Citations
“…The metasedimentary rocks involved in the western limb record two metamorphic events. A Barrovian metamorphism assisted the D 1 deformation phase with P-T conditions increasing eastwards along the SER-thrust system, and reaching ~8.5 kbar at ~650ºC (Peixoto et al 2018). Age determinations on the monazite indicated that this event took place between 575 and 565 Ma.…”
Section: The Western Limbmentioning
confidence: 94%
“…As the dominant fabric elements of the external Araçuaí orogen, the D 1 /D 2 structures record the Brasiliano event in the region, which is in turn viewed as a product of a general E-W contraction (Pedrosa-Soares et al 2001. The Barrovian metamorphism syn-kinematic to D 1 was recently dated in this region between 575 and 565 Ma (Peixoto et al 2018), the age interval of the collisional stage of the Araçuaí orogen (Pedrosa-Soares et al 2001, 2011b.…”
Section: Significance Of the Deformation Phasesmentioning
confidence: 95%
See 3 more Smart Citations